Three Nations, One Place - McCollough, Martha (Native Americans: Interdisciplinary Perspectives, 2004)
An intensive exploration of the changes experienced by the Comanches and Caddoans during Spain's occupation of the Southern Plains (1689-1921), McCollough focuses on the relationship between political and economic conditions and patterns of settlement, production and social reproduction. Challenging historical views that structure a dichotomy of the colonizers and the colonized, this study examines global, regional and local populations as it details the points of interface between Euro-American markets, Native American commodities and indigenous social groups in this early colonial period.